2007
DOI: 10.1002/anie.200603707
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic [5]Paraphenyleneacetylene: Synthesis, Properties, and Formation of a Ring‐in‐Ring Complex Showing a Considerably Large Association Constant and Entropy Effect

Abstract: In the ring: The title compound ([5]CPPA), the smallest belt‐shaped conjugated system known to date, forms a considerably stable ring‐in‐ring complex with [8]CPPA (see picture). [8]CPPA⊃[5]CPPA has a smaller contact area than [9]CPPA⊃[6]CPPA but its large Ka and ΔH values reveal that the interaction results from the electrostatic attractive force rather than the dispersion force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 66 publications
4
50
0
2
Order By: Relevance
“…An early example of “Russian doll” or “onion‐type” complexes was reported by Kawase, Oda et al. in 2004 (Figure b) . The authors found that [6]CPPA fits into the cavity of [9]CPPA and they determined a binding constant of 1180±140 m −1 (0 °C) for two π‐extended analogues ( 4 and 5 ; Figure b) that are more soluble than the parent compounds.…”
Section: Host–guest Chemistrymentioning
confidence: 99%
“…An early example of “Russian doll” or “onion‐type” complexes was reported by Kawase, Oda et al. in 2004 (Figure b) . The authors found that [6]CPPA fits into the cavity of [9]CPPA and they determined a binding constant of 1180±140 m −1 (0 °C) for two π‐extended analogues ( 4 and 5 ; Figure b) that are more soluble than the parent compounds.…”
Section: Host–guest Chemistrymentioning
confidence: 99%
“…[12] X-ray crystallographic and spectroscopic data showed that the alkyne unit of even the smallest macrocycle 1 is less bent than that of dibenzo-fused cyclooctyne.I ns tark contrast to this finding,however, macrocycle 1 undergoes rapid [2+ +2]CA-RC with TCNE at temperatures as low as 0 8 8Ci nt he absence of any catalyst, whereas cyclooctyne derivatives often require heating to react. [24][25][26] Previously reported syntheses of cycloparaphenyleneacetylenes (CPPAs) were based on 1) the brominationdehydrobromination of macrocyclic alkene precursors obtained by McMurry coupling [27][28][29][30] or 2) alkyne metathesis followed by reductive aromatization, [31] which provided access to al imited number of highly symmetric derivatives with multiple alkyne units.While the backbone-incorporated alkynes have recently been shown to undergo triple SPAAC reaction, single alkynes could not be addressed selectively owing to the increasing reactivity with each CA step. [24][25][26] Previously reported syntheses of cycloparaphenyleneacetylenes (CPPAs) were based on 1) the brominationdehydrobromination of macrocyclic alkene precursors obtained by McMurry coupling [27][28][29][30] or 2) alkyne metathesis followed by reductive aromatization, [31] which provided access to al imited number of highly symmetric derivatives with multiple alkyne units.While the backbone-incorporated alkynes have recently been shown to undergo triple SPAAC reaction, single alkynes could not be addressed selectively owing to the increasing reactivity with each CA step.…”
mentioning
confidence: 99%
“…This finding then improved the access to [6]CPPA as well. The modified McMurry coupling afforded cyclopentamer 39 , which could be smoothly converted to [5]CPPA 33 b as the smallest CPPA so far reported (Figure b) . The coupling of dialdehydes 38 and 40 (1:1 ratio) enabled production of the precursor of [7]CPPA 33 d (Figure c) .…”
Section: Angle‐strained Alkyne‐containing π‐Conjugated Macrocyclesmentioning
confidence: 99%